Faktor Penyebab Sengketa Tanah Hibah Studi Kasus di Kecamatan Pinolosian - Debi Rahmat Huntialo; Nirwan Junus; Dolot Alhasni Bakung (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The purpose of this study was to find out about the factors that cause disputes in South Bolaang Mongondow. The type of research used by researchers in preparing this study is the type of sociological juridical law research by taking an approach based on norms or legal regulations to study the process of working or interacting with law in society. The results of this study indicate that the factor causing the dispute in South Bolaang Mongondow, from the way it is done does not get a meeting point between the parties to the dispute. So much so that the unfinished permaslahan caused a dispute between the family and the village government. The impact of the dispute to the existing community so as to create conflict between the surrounding communities between the people of Hamlet 1 and Hamlet 3, until now.